CHANGING STRUCTURE OF EDUCATION AND PROFILE OF LEARNERS - Atici, Bunyamin; Bati, Ugur (Scientia Socialis, 2010)
The structure of the education suffers a great change both technologically and pedagogically with using the information and communication technologies in education. The changes which occur in the profiles of the learners become effective in experiencing these changes. The educational organizations try to respond different expectations of the learners with their problems by means of integrating the technology into the education and also the cultural differences. Now the learners could be employed with their capabilities of working in collaboration independently and adopting them to the new situations rather than the knowledge and skills owned. The changes which occur in the structure of the education are examined in the light of the profiles of the learners in this study. The study is obtained by means of interpreting the data which are obtained with the survey study which is applied to 1199 learners.
Keywords: profile of learners; ICT; paradigms